Therapeutic Effects and Molecular Mechanisms of Bioactive Compounds Against Respiratory Diseases: Traditional Chinese Medicine Theory and High-Frequency Use - Wang, Jing; Wu, Qibiao; Ding, Lu; Song, Siyu; Li, Yaxin; Shi, Li; Wang, Tan; Zhao, Daqing; Wang, Zeyu; Li, Xiangyan (Frontiers in Pharmacology, 2021)
Respiratory diseases, especially the pandemic of respiratory infectious diseases and refractory chronic lung diseases, remain a key clinical issue and research hot spot due to their high prevalence rates and poor prognosis. In this review, we aimed to summarize the recent advances in the therapeutic effects and molecular mechanisms of key common bioactive compounds from Chinese herbal medicine. Based on the theories of traditional Chinese medicine related to lung diseases, we searched several electronic databases to determine the high-frequency Chinese medicines in clinical application. The active compounds and metabolites from the selected medicines were identified using the Traditional Chinese Medicine Systems Pharmacology Database (TCMSP) by analyzing oral bioavailability and drug similarity index. Then, the pharmacological effects and molecular mechanisms of the selected bioactive compounds in the viral and bacterial infections, inflammation, acute lung injury (ALI), chronic obstructive pulmonary disease (COPD), pulmonary fibrosis, asthma, and lung cancer were summarized. We found that 31 bioactive compounds from the selected 10 common Chinese herbs, such as epigallocatechin-3-gallate (EGCG), kaempferol, isorhamnetin, quercetin, and β-sitosterol, can mainly regulate NF-κB, Nrf2/HO-1, NLRP3, TGF-β/Smad, MAPK, and PI3K/Akt/mTOR pathways to inhibit infection, inflammation, extracellular matrix deposition, and tumor growth in a series of lung-related diseases. This review provides novel perspectives on the preclinical study and clinical application of Chinese herbal medicines and their bioactive compounds against respiratory diseases.